EVALUASI SIFAT KIMIA TANAH PADA LAHAN IRIGASI PADI SAWAH (Oryza Sativa L.) DI DESA RANTELEDA KECAMATAN PALOLO KABUPATEN SIGI - Rambu Langi, Marsel Kadang; Pata’dungan, Yosep Soge; Sartika, Dwi (Fakultas Pertanian, Universitas Tadulako, 2024)
This study aims to evaluate the status of chemical properties of lowland rice soil by analyzing several parameters of the chemical elements of the soil on lowland rice fields in Ranteleda Village. This research was carried out in Ranteleda Village, Palolo District, Sigi Regency, Central Sulawesi and soil analysis was carried out at the Laboratory of Soil Science, Faculty of Agriculture, University of Tadulako and Laboratory of Analysis of Natural Resources and Environment, Faculty of Agriculture, University of Tadulako. This research was conducted from November to January 2023. The method used in this research was a survey method and the determination of the research location was carried out purposively. Sampling of disturbed soil (disturbed soil sample) using the Systematic method with 4 sampling points at a depth of 30 cm. Disturbed soil samples were then put into plastic bags and labeled which were then taken to the laboratory for analysis of the chemical nutrient content of the soil. The results of the analysis of the chemical properties of the soil showed that in the lowland rice irrigated land in Ranteleda village the N-Total values ​​were very low to low, P-Available was very high to high, K-Total was classified as moderate to low, soil pH was slightly acidic to sour, C levels -Very low to low organic, low to moderate CEC.